Kidney tonifying traditional Chinese medicine: Potential implications for the prevention and treatment of osteoporosis - Duan, Yan; Su, Yu-Ting; Ren, Jie; Zhou, Qun; Tang, Min; Li, Juan; Li, Shun-Xiang (Frontiers in Pharmacology, 2023)
The aging global population is increasingly affected by osteoporosis (OP), which is one of the most significant threats to the elderly. Moreover, its prevention and treatment situations have become increasingly severe. Therefore, it is imperative to develop alternatives or complementary drugs for preventing and treating osteoporosis. Kidney tonifying traditional Chinese medicine (KTTCM) has been used for the treatment of osteoporosis for a long time. Pharmacological studies have shown that kidney tonifying traditional Chinese medicine can promote osteoblasts, inhibit osteoclasts, and regulate the level of estrogen and plays vital roles in stimulating osteogenesis, restraining adipogenesis of marrow mesenchymal stem cells (MSCs), regulating the metabolism of calcium and phosphorus, and inhibiting oxidative stress. These effects are mediated by OPG/RANKL/RANK, BMP/Smads, MAPKs, and Wnt/β-catenin systems. To develop a safe, synergistic, effective, and homogenized TCM formula with robust scientific evidence to provide faster and more economical alternatives, the anti-osteoporosis ingredients and pharmacological mechanisms of kidney tonifying traditional Chinese medicine are recapitulated from the perspective of molecular and cell biology, and the safety and toxicity of kidney tonifying traditional Chinese medicine have also been reviewed in this paper.